2017
DOI: 10.4028/www.scientific.net/ssp.265.422
|View full text |Cite
|
Sign up to set email alerts
|

Study of Physical and Mechanical Properties of Non-Polar Rubber-Based Sealants Depending on Filler Type and Volume

Abstract: Non-curing sealants have a complex composition consisting of a mixture of polymers, plasticizers, extenders, adhesive additives, various special purpose additives (pigments, biocides, fire-retardants), and therefore the optimization of their compositions to improve the physical and mechanical and technological characteristics is rather complicated. This article demonstrates the experimental results of physical and mechanical properties such as penetration, strength, density, adhesion to metal and concrete, wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Years of experience in dealing with noise and vibrations have shown that the most effective vibration-absorbing materials are polymer composite materials with dispersed fillers, which are capable of damping due to the peculiarities of their molecular and supramolecular structure [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Years of experience in dealing with noise and vibrations have shown that the most effective vibration-absorbing materials are polymer composite materials with dispersed fillers, which are capable of damping due to the peculiarities of their molecular and supramolecular structure [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, most fillers used in the manufacture of polymer composites have a density of up to 2.5 g/cm 3 . Fillers with a higher density can be considered heavy fillers.…”
Section: Introductionmentioning
confidence: 99%